Praktik Environmental Governance dalam Inovasi Pusat Transformasi Bersama (PTB) oleh PT Freeport Indonesia atas Pembangunan Smelter Manyar - Zahrah, Farisah (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2025)
This research discusses Environmental Governance Practices in the Joint Transformation Center Innovation in supporting a balance between development and environmental management as a strategy for the construction of the Manyar Smelter by PT Freeport Indonesia. The method used in this research is descriptive qualitative using phenomenological theory through interviews, observation and documentation. The theory used in this research is the Good Environmental Governance theory according to Belbase. The research results show that the government acts as a supervisor and regulator regarding environmental management and has a limited role in the implementation of the Joint Transformation Center.